La ASEAN tras la Cumbre de Cebú: ¿en el camino de la integración? - Abad, Gracia (UNISCI Discussion Papers, 2007)
The article analyses the contributions made by the 12th ASEAN summit to the renewal process undertaken by the organisation. To this end, together with the different issues addressed over the leaders meeting, the text pays attention to the contents and the importance of the recommendations on the ASEAN Charter made by the Eminent Persons Group. Finally, the article points out some of the obstacles the member states will face in order to deepen their cooperation.